2023
DOI: 10.3390/children10081294
|View full text |Cite
|
Sign up to set email alerts
|

Child Nutrition Outcomes and Maternal Nutrition-Related Knowledge in Rural Localities of Mbombela, South Africa

Abstract: Poor nutrition outcomes among children have become one of the major public health concerns in South Africa, attributed to poor feeding practices and maternal nutrition-related knowledge with conflicting data. In view of this, a cross-sectional study was conducted to determine the association of nutrition outcomes of children aged under two years with feeding practices and maternal nutrition-related knowledge in Mbombela, South Africa. Mothers’ nutrition-related knowledge was estimated using an adapted structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
1
4
1
Order By: Relevance
“…Previous studies suggest a strong relationship between mothers' or family' knowledge and stunting [39], [40]. However, this study did not find any significance in the relationship between mothers' This may be influenced by other factors, such as economic, socio-culture, and environmental factors [41], [42]. Several respondents in the study reported that and hindered the researcher from asking the respondents to fill the questionnaire in person.…”
Section: Resultscontrasting
confidence: 80%
“…Previous studies suggest a strong relationship between mothers' or family' knowledge and stunting [39], [40]. However, this study did not find any significance in the relationship between mothers' This may be influenced by other factors, such as economic, socio-culture, and environmental factors [41], [42]. Several respondents in the study reported that and hindered the researcher from asking the respondents to fill the questionnaire in person.…”
Section: Resultscontrasting
confidence: 80%
“…Malnutrition indicators per setting showed that boys and school children in the intermediate learning phase were more likely to be stunted in the rural setting. In the urban setting, school children living in households with an income of USD 52.51 to USD 262.60/month and receiving the CSG were more likely to be thin, yet those from households with the same income of USD 52.51 to USD 262.60/month were also more likely to be overweight/obesity in the urban setting, as observed in several studies [35][36][37] and explained by the differences in the standard of living in the two settings [36]. To ensure achieving the UN's SDG goals 1, 2, and 3, the South African government introduced the National Development Plan (NDP) vision 2023, adopted in 2012 with the objective to reduce child malnutrition through eradicating poverty in all its forms, by provision of social grants [81].…”
Section: Discussionsupporting
confidence: 60%
“…in LMICs, including South Africa [71][72][73][74][75][76]. In fact, the poorer perceived health status and low quality of life among rural dwellers are attributed to a lower socio-economic status, which might affect the affordability of good nutrition to maintain proper feeding practices as well as access to health care [34,35,75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations